Biomechanical consequences of cement discoplasty: An in vitro study on thoraco-lumbar human spines - Techens, Chloé; Montanari, Sara; Bereczki, Ferenc; Eltes, Peter Endre; Lazary, Aron; Cristofolini, Luca (Frontiers in Bioengineering and Biotechnology, 2022)
With the ageing of the population, there is an increasing need for minimally invasive spine surgeries to relieve pain and improve quality of life. Percutaneous Cement Discoplasty is a minimally invasive technique to treat advanced disc degeneration, including vacuum phenomenon. The present study aimed to develop an in vitro model of percutaneous cement discoplasty to investigate its consequences on the spine biomechanics in comparison with the degenerated condition. Human spinal segments (n=27) were tested at 50% body weight in flexion and extension. Posterior disc height, range of motion, segment stiffness, and strains were measured using Digital Image Correlation. The cement distribution was also studied on CT scans. As main result, percutaneous cement discoplasty restored the posterior disc height by 41% for flexion and 35% for extension. Range of motion was significantly reduced only in flexion by 27%, and stiffness increased accordingly. The injected cement volume was 4.56±1.78 ml (mean ± SD). Some specimens (n=7) exhibited cement perforation of one endplate. The thickness of the cement mass moderately correlated with the posterior disc height and range of motion with different trends for flexions vs. extension. Finally, extreme strains on the discs were reduced by percutaneous cement discoplasty, with modified patterns of the distribution. To conclude, this study supported clinical observations in term of recovered disc height close to the foramen, while percutaneous cement discoplasty helped stabilize the spine in flexion and did not increase the risk of tissue damage in the annulus.